2005
DOI: 10.1128/iai.73.6.3342-3350.2005
|View full text |Cite
|
Sign up to set email alerts
|

The SrtA Sortase of Streptococcus agalactiae Is Required for Cell Wall Anchoring of Proteins Containing the LPXTG Motif, for Adhesion to Epithelial Cells, and for Colonization of the Mouse Intestine

Abstract: Streptococcus agalactiae (group B streptococcus [GBS]) is the leading cause of neonatal pneumonia, sepsis, and meningitis. An in silico genome analysis indicated that GBS strain NEM316 encodes 35 proteins containing an LPXTG motif which are thought to be covalently linked to the peptidoglycan by an enzyme called sortase. The role of these cell wall-anchored proteins in GBS pathogenesis was evaluated on a global level by inactivating the srtA gene. This gene encodes the major sortase SrtA that anchors most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 59 publications
2
104
1
Order By: Relevance
“…Earlier findings have shown that the fibronectin binding ability of srtA − mutants of Staphylococcus aureus (Mazmanian et al 2000) and S. agalactiae (Lalioui et al 2005) was severely hampered compared to wild type bacteria. We screened 6 vinyl sulfone drugs (by a fibronectin-binding ELISA) for their ability to inhibit the binding of Renibacterium salmoninarum to Chinook salmon fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier findings have shown that the fibronectin binding ability of srtA − mutants of Staphylococcus aureus (Mazmanian et al 2000) and S. agalactiae (Lalioui et al 2005) was severely hampered compared to wild type bacteria. We screened 6 vinyl sulfone drugs (by a fibronectin-binding ELISA) for their ability to inhibit the binding of Renibacterium salmoninarum to Chinook salmon fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…Pili are formed from polymerized proteins, which have an Nterminal conserved signal peptide and a C-terminal LPXTG motif; the LPXTG domain enabling covalent attachment of the pilus proteins to the cell-wall peptidoglycan (Lalioui et al, 2005;Nobbs et al, 2008;Ton-That & Schneewind, 2004). GBS pili have been described as contributing to GBS adhesiveness and supporting the transcytoses of the bacteria through differentiated human epithelial cells (Pezzicoli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Streptococcus gordonii, srtA inactivation leads to decreased surface protein display, reduced fibronectin binding in vitro, and a reduced ability to colonize the oral mucosa of mice (10). Likewise, srtA knockouts from Streptococcus family members S. mutans (11), S. pneumonia (12), S. pyogenes (13), S. suis (14), S. sanguinis (15), and S. agalactiae (16) have been shown to have attenuated pathogenicity.…”
mentioning
confidence: 99%